Long Non-coding RNA H19 Regulates Porcine Satellite Cell Differentiation Through miR-140-5p/SOX4 and DBN1 - Li, Jingxuan; Su, Tao; Zou, Cheng; Luo, Wenzhe; Shi, Gaoli; Chen, Lin; Fang, Chengchi; Li, Changchun (Frontiers in Cell and Developmental Biology, 2020)
The H19 gene promotes skeletal muscle differentiation in mice, but the regulatory models and mechanisms of myogenesis regulated by H19 are largely unknown in pigs. Therefore, the regulatory modes of H19 in the differentiation of porcine skeletal muscle satellite cells (PSCs) need to be determined. We observed that H19 gene silencing could decrease the expressions of the myogenin (MYOG) gene, myogenic differentiation (MYOD), and myosin heavy chain (MYHC) in PSCs. Therefore, we constructed and sequenced 12 cDNA libraries of PSCs after knockdown of H19 at two differentiation time points to analyze the transcriptome differences. A total of 11,419 differentially expressed genes (DEGs) were identified. Among these DEGs, we found through bioinformatics analysis and protein interaction experiment that SRY-box transcription factor 4 (SOX4) and Drebrin 1 (DBN1) were the key genes in H19-regulated PSC differentiation. Functional analysis showed that SOX4 and DBN1 promote PSC differentiation. Mechanistically, H19 regulates PSC differentiation through two different pathways. On the one hand, H19 functions as a molecular sponge of miR-140-5p, which inhibits the differentiation of PSCs, thereby modulating the derepression of SOX4. On the other hand, H19 regulates PSC differentiation through directly binding with DBN1. Furthermore, MYOD binds to the promoters of H19 and DBN1. The knock down of MYOD inhibits the expressions of H19 and DBN1. We determined the function of H19 and provided a molecular model to elucidate H19’s role in regulating PSC differentiation